2014
DOI: 10.3109/08880018.2014.886316
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Menorrhagia and Bleeding Disorders in University Students

Abstract: Menorrhagia is a common but mostly unrecognized and untreated problem among university students. Underlying bleeding disorders are not rare and require comprehensive hemostatic evaluation for identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 38 publications
1
46
0
4
Order By: Relevance
“…T3, T4, TSH estimation should be made mandatory in cases of dysfunctional uterine bleeding to detect apparent and occult hypothyroidism. 4 In studies by Trasi et al 5 Kadir et al 1 and Gursel et al 2 inherited coagulopathy accounted for 19.16%, 17% and 15% of cases of menorrhagia respectively. This is similar to our result of 18%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T3, T4, TSH estimation should be made mandatory in cases of dysfunctional uterine bleeding to detect apparent and occult hypothyroidism. 4 In studies by Trasi et al 5 Kadir et al 1 and Gursel et al 2 inherited coagulopathy accounted for 19.16%, 17% and 15% of cases of menorrhagia respectively. This is similar to our result of 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that inherited bleeding disorder, especially in mild form, is the underlying cause in a large number of women with menorrhagia and the incidence may be as high as 15%. 2 Menorrhagia may ultimately lead to surgery. 3 therefore patient having menorrhagia without obvious pelvic pathology should be routinely studied to diagnose underlying endocrine and hemostatic disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, one case of a 12 year-old adolescent girl with moderate factor X deficiency (plasma factor 2 %) was referred to our clinic with a complaint of severe menorrhagia starting from just after menarche and when her detailed history was taken it was learnt that she had had severe gingival bleeding following a dental procedure. In a recent study, Gursel T et al studied 376 university students and 82 of them showed menorrhagia with a quantitative assessment of bleeding with PBAC and they found two patients with clotting factor deficiency: one of them with mild factor XI deficiency and the other with mild factor VII deficiency [21]. We think that our finding was different because the factor X deficiency is seen at a relatively higher frequency in our region than other parts of Turkey due to the high rates of parental consanguinity in the eastern part of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Clotting factor deficiencies are the least common bleeding disorder, as a cause of menorrhagia. It is reported that the most common clotting deficiency is factor XI and it occurs in 1.0-11.9 % of women with menorrhagia [21]. In our study, one case of a 12 year-old adolescent girl with moderate factor X deficiency (plasma factor 2 %) was referred to our clinic with a complaint of severe menorrhagia starting from just after menarche and when her detailed history was taken it was learnt that she had had severe gingival bleeding following a dental procedure.…”
Section: Discussionmentioning
confidence: 99%